Thigh muscularity and sprinting performance of national-level long-distance runners - Ando, R.; Tanji, F.; Ohnuma, H.; Ikeda, T.; Yamanaka, R.; Suzuki, Y. (Journal of Human Kinetics, 2022)
Long-distance runners require aerobic capacity as well as sprinting ability for superior performance; however, the factors which determine the sprinting ability of long-distance runners remain undetermined. Therefore, the purpose of our study was to examine the association between thigh muscle size and sprinting ability in national-level male long-distance runners. Nineteen male long-distance runners with 5000 m personal-best times of 13:12.63-14:14.87 participated in this study, and transaxial images of their right thighs were collected using magnetic resonance imaging. The cross-sectional areas of the quadriceps femoris, hamstrings, and adductor muscles were calculated from the transaxial images at 30%, 50%, and 70% of the distance from the greater trochanter to the lower edge of the femur; these areas were normalized by body mass. Sprint times for 100 m and 400 m were recorded on an all-weather track. The results revealed positive correlations between the normalized cross-sectional areas of the quadriceps femoris at 50% and 70% of the thigh length and the 100 m (r = 0.666, p = 0.002 and r = 0.531, p = 0.019, respectively) and 400 m sprint times (r = 0.769, p < 0.001 and r = 0.580, p = 0.009, respectively); hence, the larger the quadriceps, the slower the sprint speed. However, no association was found between the normalized cross-sectional areas of the hamstrings or adductor muscles and sprinting performance. Therefore, running motions which activate the quadriceps femoris much more than the hamstrings and adductor muscles should be avoided by national-level long-distance runners.